2017
DOI: 10.1371/journal.pone.0181243
|View full text |Cite
|
Sign up to set email alerts
|

Feedback activation of AMPK-mediated autophagy acceleration is a key resistance mechanism against SCD1 inhibitor-induced cell growth inhibition

Abstract: Elucidating the bioactive compound modes of action is crucial for increasing success rates in drug development. For anticancer drugs, defining effective drug combinations that overcome resistance improves therapeutic efficacy. Herein, by using a biologically annotated compound library, we performed a large-scale combination screening with Stearoyl-CoA desaturase-1 (SCD1) inhibitor, T-3764518, which partially inhibits colorectal cancer cell proliferation. T-3764518 induced phosphorylation and activation of AMPK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 47 publications
3
21
0
Order By: Relevance
“…A distinct mechanism has been shown to render cancer cells partially resistant to the suppression of SCD1 activity. The treatment of cancer cells with the SCD1 inhibitor, CVT-11127, caused adenosine monophosphate-activated protein kinase (AMPK) activation via phosphorylation at Thr172, which in turn led to inactivation of the phosphorylation of ACC at Ser79 [78,91]. The carboxylation of acetyl-CoA by ACC generates malonyl-CoA, the substrate for chain elongation in FA biosynthesis [127].…”
Section: Scd1 Inhibitors In Combined Therapymentioning
confidence: 99%
See 3 more Smart Citations
“…A distinct mechanism has been shown to render cancer cells partially resistant to the suppression of SCD1 activity. The treatment of cancer cells with the SCD1 inhibitor, CVT-11127, caused adenosine monophosphate-activated protein kinase (AMPK) activation via phosphorylation at Thr172, which in turn led to inactivation of the phosphorylation of ACC at Ser79 [78,91]. The carboxylation of acetyl-CoA by ACC generates malonyl-CoA, the substrate for chain elongation in FA biosynthesis [127].…”
Section: Scd1 Inhibitors In Combined Therapymentioning
confidence: 99%
“…The carboxylation of acetyl-CoA by ACC generates malonyl-CoA, the substrate for chain elongation in FA biosynthesis [127]. The suppression of FA synthesis in response to SCD1 inhibition has been postulated to protect cells from the excessive accumulation of SFAs, whereas the synthesis of MUFAs is impaired [78,91]. The mechanisms of the lipotoxicity of SFAs and cytoprotective effect of MUFAs were thoroughly discussed by Nolan and Larter [128].…”
Section: Scd1 Inhibitors In Combined Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…To date, several studies have shown that SCD1 deficiency triggers activation of the AMPK signaling pathway in the liver [ 48 ], skeletal muscles [ 20 ], and cancer cell lines [ 49 , 50 ]. The AMPK-mediated actions of SCD1 also include autophagy-dependent cell growth and death [ 49 , 50 ], FA β-oxidation [ 48 ], and histone acetylation [ 20 ]. Consistent with previous studies of other tissues, we found that the loss of SCD1 expression activated AMPK in pancreatic islets and INS-1E cells.…”
Section: Discussionmentioning
confidence: 99%